Monetary policy at the zero lower bound. Geldpolitik an der Null-Zins-Grenze - Cabos, Karen (Estonian Discussions on Economic Policy, 2015)
Both interest rates and inflation rates in the Euro area have reached levels dangerously close to zero. By the strategy of quantitative easing the ECB has been providing ample liquidity – yet without lasting success. Several asymmetries in policy transmission and monetary policy making have been acknowledged when interest rates hit the zero bound. This paper starts with a short review of these asymmetries. Afterwards it turns to the issues of credibility and commitment. It is argued that the inflation forecasts of the ECB are central for the communication strategy. In the current situation they should signal the willingness to stick to low interest rates. Yet the ECB is shown to be rather more optimistic than other forecasters when the prevailing threats of deflation are concerned